Mechanism of Resource Virtualization in RCS for Multitask Stream Applications. (22nd September 2010) - Kirischian, L.; Dumitriu, V.; Chun, P. W.; Okouneva, G.
Abstract : Virtualization of logic, routing, and communication resources in recent FPGA devices can provide a dramatic improvement in cost-efficiency for reconfigurable computing systems (RCSs). The presented work is "proof-of-concept" research for the virtualization of the above resources in partially reconfigurable FPGA devices with a tile-based architecture. The following aspects have been investigated, prototyped, tested, and analyzed: (i) platform architecture for hardware support of the dynamic allocation of Application Specific Virtual Processors (ASVPs), (ii) mechanisms for run-time on-chip ASVP assembling using virtual hardware Components (VHCs) as building blocks, and (iii) mechanisms for dynamic on-chip relocation of VHCs to predetermined slots in the target FPGA. All the above mechanisms and procedures have been implemented and tested on a prototype platform—MARS (multitask adaptive reconfigurable system) using a Xilinx Virtex-4 FPGA. The on-chip communication infrastructure has been developed and investigated in detail, and its timing and hardware overhead were analyzed. It was determined that component relocation can be done without affecting the ASVP pipeline cycle time and throughput. The hardware overhead was estimated as relatively small compared to the gain of other performance parameters. Finally, industrial applications associated with next generation space-borne platforms are discussed, where the proposed approach can be beneficial.